The susceptibility of Trypanosoma congolense isolated in Zambézia Province, Mozambique, to isometamidium chloride, diminazene aceturate and homidium chloride - S. Jamal; I. Sigauque; C. Macuamule; L. Neves; T. Marcotty; B.L. Penzhorn; P. Van den Bossche (Onderstepoort Journal of Veterinary Research, 2005)
Resistance to trypanocidal drugs has been detected in various African countries and is a serious impediment to the control of livestock trypanosomosis. To determine whether drug resistant trypanosome strains are present in the Zambézia Province of Mozambique a study was initiated. To assess the effect of the farming system and the drug-use regimen on the development of drug resistance, trypanosome isolates were collected from cattle from subsistence and commercial livestock production systems. The susceptibility of seven isolates against isometamidium chloride, diminazene aceturate and homidium chloride was tested in mice using a multiple-dose test. In four of the seven isolates high levels of drug resistance to diminazene aceturate and isometamidium chloride were detected. In most cases the observed levels of drug resistance correlated with the drug-use practices in the particular livestock production system.